2006
DOI: 10.1523/jneurosci.5566-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Aging-Dependent Alterations in Synaptic Plasticity and Memory in Mice That Overexpress Extracellular Superoxide Dismutase

Abstract: Oxidative damage caused by reactive oxygen species (ROS) has been proposed to be critically involved in several pathological manifestations of aging, including cognitive dysfunction. ROS, including superoxide, are generally considered as neurotoxic molecules whose effects can be alleviated by antioxidant enzymes. However, ROS also are known to be necessary components of the signal transduction cascades underlying normal synaptic plasticity. Therefore, we reasoned that the role that ROS and antioxidant enzymes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(126 citation statements)
references
References 29 publications
4
119
2
Order By: Relevance
“…1 A). We then measured the levels of superoxide in the hippocampus by using dihydroethidium (DHE) staining (16). We found that Tg2576 mice exhibited higher levels of hippocampal superoxide compared with WT littermates (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 A). We then measured the levels of superoxide in the hippocampus by using dihydroethidium (DHE) staining (16). We found that Tg2576 mice exhibited higher levels of hippocampal superoxide compared with WT littermates (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…DHE was obtained from Molecular Probes. To identify superoxide formation in the brain, DHE was used as previously described (16). Briefly, DHE-injected animals were cardiac-perfused with 4% paraformaldehyde, their were brains sectioned on a cryostat, and then sections were mounted with Vectashield H1200 containing DAPI (Vector Laboratories).…”
Section: Methodsmentioning
confidence: 99%
“…This series of studies addresses a basic question regarding the mechanism by which lifelong exercise can act to limit the extent of cerebellar damage [1,20,31] and loss of cerebellar motor function [9,19]. These results indicate that aging is coupled to an increase in cerebellar oxidative damage for a broad array of molecules.…”
Section: Discussionmentioning
confidence: 95%
“…Our recent work on another SOD isozyme, extracellular SOD (EC-SOD), revealed that EC-SOD overexpression improves hippocampal synaptic plasticity and memory-related behavioral performance in aged mice (Hu, Serrano, Oury, & Klann, 2006). In light of our observations with EC-SOD transgenic mice, we utilized SOD-2 overexpressing mice to examine the role of mitochondrial superoxide on hippocampal function during aging.…”
Section: Introductionmentioning
confidence: 99%